2006
DOI: 10.1371/journal.ppat.0020120
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of T-Cell Responses by the Cryptococcus Capsular Polysaccharide Glucuronoxylomannan

Abstract: The major virulence factor of the pathogenic fungi Cryptococcus neoformans and C. gattii is the capsule. Glucuronoxylomannan (GXM), the major component of the capsule, is a high-molecular-weight polysaccharide that is shed during cryptococcosis and can persist in patients after successful antifungal therapy. Due to the importance of T cells in the anticryptococcal response, we studied the effect of GXM on the ability of dendritic cells (DCs) to initiate a T-cell response. GXM inhibited the activation of crypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 49 publications
3
78
0
Order By: Relevance
“…In contrast to the unmasking form of cryptococcal IRD, relapsing cases are culture negative, supporting the hypothesis that residual cryptococcal antigen is the precipitating factor. Higher opening cerebrospinal fluid (CSF) pressures are observed in cryptococcal IRD patients (67,130,154). These may reflect delayed clearance of residual antigen from the leptomeninges and the precipitating inflammation induced by a Th1 response following ART.…”
Section: Cryptococcal Ird: Severe Consequences Of a High Antigen Loadmentioning
confidence: 99%
“…In contrast to the unmasking form of cryptococcal IRD, relapsing cases are culture negative, supporting the hypothesis that residual cryptococcal antigen is the precipitating factor. Higher opening cerebrospinal fluid (CSF) pressures are observed in cryptococcal IRD patients (67,130,154). These may reflect delayed clearance of residual antigen from the leptomeninges and the precipitating inflammation induced by a Th1 response following ART.…”
Section: Cryptococcal Ird: Severe Consequences Of a High Antigen Loadmentioning
confidence: 99%
“…DCs were enriched by positive selection with CD11c ϩ magnetic beads. Mitomycin (50 g/ml)-treated DCs from wild-type mice were plated at 1 ϫ 10 4 per well in 96-well round-bottom plates (19,39). Statistics.…”
Section: Cd4mentioning
confidence: 99%
“…C57BL/6 mice are relatively susceptible to cryptococcosis (6), and a virulent encapsulated strain of C. neoformans was used for the mortality studies. Moreover, glucuronoxylomannan, the major component of the cryptococcal capsule, directly inhibits T-cell responses (30,39). Thus, while MR-dependent immune responses to MP contribute to host defenses against cryptococcosis, they do not mediate fully protective responses in the mouse model.…”
Section: Vol 76 2008 Susceptibility Of Mr Ko Mice To Cryptococcosismentioning
confidence: 99%
“…Previous studies indicated that one of the capsular components of C. gattii may have been involved in immune avoidance or immune suppression and was required for the complete virulence of C. gattii (12,13). Because C. gattii can induce immune avoidance or suppression, an analysis of loss-of-function using gene knockout (KO) mice is not applicable for studying any protective immune responses against C. gattii, and the protective immunity against highly virulent C. gattii has not been well characterized.…”
mentioning
confidence: 99%